(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Some of the states in India claimed they already created a smart city. Principally the claim based mostly of IT utilization for their governance. This section focuses on the present relationships among governance and smart cities, specifically within the smart city literature. There is no clear definition regarding the smart city governance. In general, a smart city definition is to explain a developed geographic region that makes property economic development and prime quality of life by excelling in - (1) government of a smart city, (2) smart decision-making, (3) smart administration and (4) smarttown collaboration. In turn, I address the governance in smart cities as a replacement sort of collaboration through the employment of ICTs. In this paper I will discuss two important terms Great Governance Index (GGI) and Data Governance. The aim is to map e-government condition by measure indicators of smart government, that are: clear governance and open information for the general public. Thus, new and innovative sorts of governance area unit required to deal with the challenges of smart cities going on the far side the standard establishments and therefore the classical processes of governing (Bolívar, 2016). This analysis is outbound from public info revealing law and to correspond with the existence law. By examining government transparency, the output of the analysis will be accustomed live the effectiveness of public info revealing law and to see the condition of e-government in authorities within which as a part of a smart city.